The Spiritual Aspect of Pain: An Integrative Review - De-Diego-Cordero, Rocío (Journal of religion and health, 2024)
Pain is an unpleasant sensory and emotional experience that affects individuals in various ways involving biological, psychological, social, and spiritual aspects. There is currently no comprehensive treatment that effectively addresses all aspects of pain. This integrative review aimed to analyze the spiritual aspect of pain relief. Following the specified methodological criteria, a total of 20 articles were selected. There evidenced a lack of spiritual care provided by healthcare professionals, even though its correlation with pain and its potential benefits have been widely demonstrated in the literature. Fortunately, some patients put into practice existential and religious tools to self-control and cope with their pain, although not always with a successful response.